Real-world efficacy, safety, and clinical outcomes of ombitasvir/paritaprevir/ritonavir ± dasabuvir ± ribavirin combination therapy in patients with hepatitis C virus genotype 1 or 4 infection: The Turkey experience experience - Aygen, Bilgehan; Demirtürk, Neşe; Yıldız, Orhan; Çelen, Mustafa Kemal; Çelik, İlhami and Barut, Şener and Ural, Onur and Batırel, Ayşe and Mıstık, Reşit and Şimşek, Funda and et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: mbitasvir/paritaprevir/ritonavir (OMV/PTV/r) ± dasabuvir (DSV) ± ribavirin (RBV) combination has demonstrated excellent rates of sustained virologic response (SVR) and a very good safety profile in patients with the chronic hepatitis C virus (HCV) genotype 1 or 4 infections. We aimed to investigate the effectiveness and safety of OMV/PTV/r ± DSV ± RBV combination regimen in a real-world clinical practice. Materials and Methods: Data from HCV genotype 1 and 4 patients treated with OMV/PTV/r ± DSV ± RBV (n=862) in 34 centers across Turkey between April 1, 2017 and August 31, 2018 were recorded in a large national database. Demographic, clinical, and virologic data were analyzed. Results: The mean age of the patients was 55.63, and 430 patients (49.9%) were male. The majority had HCV genotype 1b infection (77.3%), and 66.2% were treatment-naïve. Non-cirrhosis was present at baseline in 789 patients (91.5%). SVR12 rate was 99.1% in all patients. Seven patients had virologic failure. No significant differences were observed in SVR12 according to HCV genotypes. HCV RNA was undetectable at treatment week 4 in 90.9%, at treatment week 8 in 98.5%, and at the end of treatment (EOT) in 98.9%. SVR12 ratio was significantly higher in the non-cirrhotic patients compared to that in the compensated cirrhotic patients. Rates of adverse events (AEs) in the patients was 59.7%. Conclusion: The present real-life data of Turkey for the OBV/PTV/r ± DSV ± RBV treatment of patients with HCV genotype 1b, 1a, or 4 infection from 862 patients demonstrated high efficacy and a safety profile.